Epigenetic modulation and prostate cancer: Paving the way for NK cell anti-tumor immunity - dos Reis, Filipa D.; Jerónimo, Carmen; Correia, Margareta P. (Frontiers in Immunology, 2023)
Immunoepigenetics is a growing field, as there is mounting evidence on the key role played by epigenetic mechanisms in the regulation of tumor immune cell recognition and control of immune cell anti-tumor responses. Moreover, it is increasingly acknowledgeable a tie between epigenetic regulation and prostate cancer (PCa) development and progression. PCa is intrinsically a cold tumor, with scarce immune cell infiltration and low inflammatory tumor microenvironment. However, Natural Killer (NK) cells, main anti-tumor effector immune cells, have been frequently linked to improved PCa prognosis. The role that epigenetic-related mechanisms might have in regulating both NK cell recognition of PCa tumor cells and NK cell functions in PCa is still mainly unknown. Epigenetic modulating drugs have been showing boundless therapeutic potential as anti-tumor agents, however their role in immune cell regulation and recognition is scarce. In this review, we focused on studies addressing modulation of epigenetic mechanisms involved in NK cell-mediated responses, including both the epigenetic modulation of tumor cell NK ligand expression and NK cell receptor expression and function in different tumor models, highlighting studies in PCa. The integrated knowledge from diverse epigenetic modulation mechanisms promoting NK cell-mediated immunity in various tumor models might open doors for the development of novel epigenetic-based therapeutic options for PCa management.